2006
DOI: 10.1186/1471-2407-6-156
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic features and genetic characterization of male breast cancer families: identification of two recurrent BRCA2 mutations in north-east of Italy

Abstract: Background: Breast cancer in men is an infrequent occurrence, accounting for ~1% of all breast tumors with an incidence of about 1:100,000. The relative rarity of male breast cancer (MBC) limits our understanding of the epidemiologic, genetic and clinical features of this tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
0
12
1
Order By: Relevance
“…BRCA1/2 mutations were more prevalent in men with a positive first-degree FH (17.9%) compared with those without (6.3%) and a threefold association emerged between a positive FH and carrier status, falling short of the level of statistical significance. It has been previously reported that BRCA1/2 mutations are more frequent in MBCs with a positive FH [23,29,33]. However, in our series, 50% of the mutations were identified in MBC cases without FH, thus from a clinical point of view, our data indicate that mutation screening is beneficial also among isolated MBC cases.…”
Section: Discussioncontrasting
confidence: 64%
“…BRCA1/2 mutations were more prevalent in men with a positive first-degree FH (17.9%) compared with those without (6.3%) and a threefold association emerged between a positive FH and carrier status, falling short of the level of statistical significance. It has been previously reported that BRCA1/2 mutations are more frequent in MBCs with a positive FH [23,29,33]. However, in our series, 50% of the mutations were identified in MBC cases without FH, thus from a clinical point of view, our data indicate that mutation screening is beneficial also among isolated MBC cases.…”
Section: Discussioncontrasting
confidence: 64%
“…Not surprisingly, BRCA mutations are found more often in men with a first-degree relative diagnosed with breast cancer (23). This highlights the importance of attention to family history by both physicians and patients, and of communication among family members.…”
Section: -------------------------------------------------mentioning
confidence: 92%
“…The lifetime risk for breast cancer in a male BRCA2 mutation carrier is ~7%, 80-100 times higher than for the general population (15,16,21). It is estimated that 4-40% of MBC patients carry a mutation in BRCA2 (12,(22)(23)(24). However, a precise estimate is limited because few studies have included populations of males who were not already diagnosed with breast cancer.…”
Section: Risk Factors For Mbcmentioning
confidence: 99%
“…We amplified patient tumor and blood DNA for two markers within BRCA1 (D17S855 and D17S1322) and four markers around BRCA2 (D13S290, D13S260, D13S1698, and D13S171). The heterozygosity for these markers ranged from 0.46 to 0.82 [17, 26]. Primer sequences and distance from BRCA1 or BRCA2 are given in Additional file 1 (Table S2).…”
Section: Methodsmentioning
confidence: 99%